THE INFLUENCE OF WORK EXPERIENCE AND ENVIRONMENTAL UNCERTAINTY ON EMPLOYEE PERFORMANCE MEDIATED BY WORK FLEXIBILITY IN HUMAN RESOURCE PRACTICES IN REGIONAL OFFICE EMPLOYEES OF THE DIRECTORATE GENERAL OF TAXES NORTH SUMATRA I KPP PRATAMA MEDAN POLONIA - Gracemonn Sitompul; Yeni Absah; R. Hamdani Harahap (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The performance of employees at the Medan Polonia KPP Pratama Office is not yet optimal, which is reflected in the level of errors in tasks and non-achievement of targets. Apart from that, low work flexibility can be seen from the difficulty of employees adapting. The experience of working in the office is still not strong, especially in switching from offline to online work after the pandemic. Uncertainty in the work environment also affects employee effectiveness and efficiency. This research aims to test and analyze the impact of various factors such as work flexibility, work experience and environmental uncertainty on employee performance. This research uses quantitative descriptive methods. The research sample was 100 KPP Pratama Medan Polonia employees. Data collection was carried out through distributing questionnaires and data analysis was carried out using the SmartPLS application. The research results show that Work Experience and Work Flexibility have a positive effect on improving employee performance, with Work Flexibility also acting as a mediator in this relationship. In contrast to Environmental Uncertainty, this variable has been proven to have a negative effect on Employee Performance.